Plant cell morphogenesis methods and protocols - Cvrčková, Fatima 1966-; Žárský, Viktor 1958- (Methods in Molecular Biology, 2019)
This book collects techniques to continue exploring post-genomic land plant biology though the wisdom and skills accumulated from work on the founding molecular biology models that can now guide research into other species, including crop plants. Beginning with the visualization of plant cell structures, the volume moves on to cover digital image analysis protocols, qualitative and quantitative detection of the organization and dynamics of individual intracellular structures, the manipulation of intracellular structures, as well as techniques for studying model cell types. Written for the highly successful Methods in Molecular Biology series, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and fully updated, Plant Cell Morphogenesis: Methods and Protocols, Second Edition serves as an ideal source of inspiration for further research into the morphogenesis of plant cells, tissues, and organs